Nilai Sosial dan Budaya dalam Naskah Drama Gerbong Karya Agam Wispi : (Kajian Antropologi Sastra) - Wildan Aldiansyah; Siti Nur Cholisha; Irfa Rufaidah; Piona Levania (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study examines the social and cultural values in the drama script Gerbong by Agam Wispi through a literary anthropology approach. The research is grounded in the role of literature as a reflection of socio-cultural values, with Gerbong selected for its rich portrayal of post-revolution Indonesian societal dynamics, which has yet to be holistically analyzed from an anthropological perspective. The aim is to identify the manifestations of socio-cultural values through dramatic structures such as dialogue, characterization, and conflict. A qualitative descriptive method was employed, analyzing narrative and symbolic elements within the script. Findings reveal that social values are reflected in non-familial solidarity, critiques of revolutionary injustice, humanism amid adversity, and women’s resistance to stigmatization. Cultural values emerge through the gerbong (train carriage) as a metaphor for resilience, collective sacrifice, and a belief in independence preserved through oral traditions. Intergenerational conflicts between colonial and post-independence values highlight cultural dynamics in postcolonial transition. The study recommends integrating the script into educational curricula, exploring its performative dimensions, and conducting further interdisciplinary research on power relations and gender representation.